Effects of aging of ferric-based drinking water sludge on its reactivity for sulfide and phosphate removal. (1st October 2020) - Salehin, Sirajus; Kulandaivelu, Jagadeesh kumar; Rebosura, Mario; van der Kolk, Olaf; Keller, Jürg; Doederer, Katrin; Gernjak, Wolfgang; Donose, Bogdan C.; Yuan, Zhiguo; Pikaar, Ilje
Highlights: Akaganeite is the main iron oxide species in ferric DWS Akaganeite transforms from amorphous to more crystalline form during DWS aging Sulfide removal capacity of ferric DWS decreases with increased sludge age Aeration during activated sludge treatment breaks the crystalline form of akaganeite Enhanced P removal in WWTPs can be achieved by using ferric DWS Abstract: Recent studies demonstrated the practical potential of multiple beneficial reuse of ferric-rich drinking water sludge (ferric DWS) for sulfide and phosphate removal in wastewater applications. In practice, ferric DWS is often stored on-site for periods ranging from days to several weeks (or even months), which may affect its reuse potential through changes in iron speciation and morphology. In this study, we investigated for the first time the impact of ferric DWS 'aging' time on the iron speciation and morphology and its subsequent impact on its reactivity and overall sulfide and phosphate removal capacity. A series of coagulation tests were conducted to generate ferric DWS of a practically relevant composition by using raw influent water from a full-scale drinking water treatment plant (DWTP). A comparison with ferric DWS from 8 full-scale DWTPs confirmed the similitude. The presence of akaganeite ( β -FeOOH) was detected in ferric DWS (through XRD analyses), independent of the DWS storage time. However, the morphology of akaganeite changed over time from a predominant poorly-crystalline phase in 'fresh' DWS (8 ± 0.1% of total Fe) to a highly crystalline phase (76 ± 3% of total Fe) at a sludge aging time of 30 days which was confirmed by means of Rietveld refinement in XRD analyses (n = 3). Subsequent batch tests showed that its sulfide removal capacity decreased significantly from 1.30 ± 0.02 mmol S/mmol Fe (day 1) to 0.60 ± 0.01 (day 30), a decrease of 54 % ( p  < 0.05). The level of crystallinity however had no impact on sulfide removal kinetics, most sulfide being removed within 10 minutes. Upon aeration of sulfide-loaded ferric DWS in activate sludge, amorphous iron oxides species were formed independent of the initial DWS crystallinity which resulted in efficient P removal at capacities similar to that of conventional FeCl3 dosing.